THE INFLUENCE OF FUNDING AND RESEARCH AND DEVELOPMENT DECISIONS ON THE VALUE OF COMPANIES WITH PROFIT GROWTH AS MODERATION - Yusuf Hendrawan; Endang Ruhiyat; Suripto (ZILLZELL MEDIA PRIMA, 2025)
This study aims to obtain empirical evidence of the influence of Funding Decisions and Research and Development on Company Value with Profit Growth as a moderation. This type of research is quantitative associative. The population in this study is primary consumer goods sector companies listed on the Indonesia Stock Exchange in 2019-2023. The determination of samples by purposive sampling technique was obtained from 78 companies with 390 observation data. The analysis technique and hypothesis testing were carried out by panel data regression analysis through eviews ver-12. Based on the t-test, it is known that the variables of funding decisions affect the value of the company and research and development do not affect the value of the company. Meanwhile, profit growth can moderate the influence of funding decision variables on company value and profit growth cannot moderate the influence of research and development on company value.